Problems of Russian Church diaspora in Finland, with the story of Valaam monastery in the interwar period as an example - Tatyana Shevchenko (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. II, Istorii͡a︡, istorii͡a︡ Russkoĭ pravoslavnoĭ t͡s︡erkvi, 2022)
The article examines the period of the history of the Transfiguration of the Valaam Monastery of 1918 - 1939, before the evacuation to Heyniavesi. The famous Russian monastery, which belonged to the Diocese of Finland and Vyborg of the Orthodox Russian Church, had to adapt to life in independent Finland. The conditions of the monastery existence had changed significantly after the declaration of independence of this country and the change of the state system in Russia. In 1918, the Finnish government awarded the diocese the status of the second state church of the national minority. Despite the difficulties of socio-political, economic and jurisdictional nature, active finnization, which included the imposed calendar reform, the monastery became a symbol of steadfastness, evidence of the greatness of Russian culture and loyalty to Orthodoxy for Russian emigration around the world. The monastery leadership managed to find a common language with the church and secular authorities of Finland, the monastery won the respect and love of ordinary Finlanders. It can be said that the monastery has found its place in a new Western society. However, the author believes that it is possible to assert about the "prosperity" or "flourishing" of the Valaam Monastery at that time only conditionally, in comparison with the sad fate of monasteries in the USSR. She recalls the contradictory events in the story of the Valaam Monastery in the period, which influenced the fate of its inhabitants and the monastery itself, contributed to the reduction in the number of the brotherhood and the appearance of a "split" in it, and proves that visible well-being was the attribute of an artificially created image, although it had a positive meaning.